HEALTH - Sriwulandari, Atik (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
A healthy human is not only a sound body, but also spiritually healthy. So healthy and ideal body in terms of health aspects of physical, mental and social and not only free of disease (WHO Definition of Health 1950). All these aspects will affect the appearance or performance of each individual, in performing daily activities like work, work, be creative and do things that are productive and useful. Health, education and income of every individual are the three main factors which influence the quality of human resources. Therefore, every individual has the right and must always maintain good health, which is the main capital in order to live productive, happy and prosperous.